World Bank East Asia and Pacific Economic Update, October 2013 : Rebuilding Policy Buffers, Reinvigorating Growth - World Bank (Washington, DC, 2013)
Global growth momentum accelerated during the second and third quarters of 2013, while many downside risks lingered in the background. Strengthening of global growth momentum will help developing East Asia maintain a growth rate in excess of 7 percent, retaining its status as the global growth leader. Domestic demand, which has been the main driver of growth in the East Asia and Pacific (EAP) region in the post-global financial crisis period, is slowing. The decision by the United States (U.S.) Federal Reserve (Fed) to delay tapering of quantitative easing (QE) has restored capital flows to emerging markets, giving the authorities a second opportunity to take measures to lower risks from future volatility. As the global growth cycle undergoes change, adjustments to fiscal and monetary policy are warranted in many EAP countries. With growth running at or above potential for most countries in the region, progress at upgrading growth and reducing poverty depends crucially on structural reforms. While the balance of risks to base case regional forecast lies on the downside, several upside risks have recently emerged. The three immediate headline risks include a less orderly tapering of the U.S.'s unconventional monetary policies, prolonged fiscal deadlock in the U.S., and a sharper than expected slowdown of the Chinese economy. In this context, the report is divided into following three parts: part one is recent developments and outlook; part two is selected emerging issues; and part three is the medium-term development agenda.